Nutritional Infertility and Ameliorative Measures in Dairy Animals of Middle Gujarat - Dhami, A.J.; Patel, J.A.; Hadiya, K.K.; Parmar, S.C.; Chaudhari , D.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Fertility improvement camps were organized in different villages of middle Gujarat covering 1481 breedable cattle and buffaloes with the history of impaired fertility. The reproductive status of animals was ascertained through gynaeco-clinical examination per rectum. Blood sampling (n=305) was done from representative groups of animals to know the nutritional status. All non-infectious infertile animals were dewormed using either Inj. Ivermectin 100 mg s/c or bolus Fenbendazole + Ivermectin 3.0 g orally. Anestrus animals (n=265) were then nutritionally supplemented either with chelated area specific mineral mixture (ASMM, 50-60 g/d/h) or multi-minerals boli - one on alternate day, with and without bypass fat (75-80 g/d/h) for one month along with an advice to improve feeding level, estrus detection and timely breeding. Revisits were made after 2.5-3.0 months to check the reproductive status. The mean blood glucose concentrations were significantly lower (p
Keywords: Dairy animals; Non-infectious infertility; Nutritional supplements; Estrus response; Conception rate